Sustainable foreign direct investment: the need for adapting international investment laws to mitigate inequality - Halim, Daiyaan (My University, 2021)
This paper considers whether sustainable foreign direct investment (FDI) in the renewable energy sector can reduce or mitigate inequality in developing countries within the framework of current international investment agreements (IIAs) and World Trade Organisation (WTO) rules. The paper utilises political systems theory to evaluate the policies that inform international investment laws and those necessary to promote development and inequality reductions. Drawing on principles of economics, it considers the effects of competition and deindustrialisation on labour markets and the role of skills-biased technological change in perpetuating inequality. To reduce inequality states must enter gateway activities within renewable energy value chains, upgrade domestic industries along the value chains, and limit competition. The paper recommends that states harness policy to attract investment within escalator industries, develop local productive capacity by generating demand and ensuring the transfer of skills, and put measures in place to mitigate inequality. However, the rules of international investment law limit the policy options available to states to realise these developmental outcomes. The paper concludes that if sustainable FDI is to avoid perpetuating inequality, legal reform is necessary to limit competition and increase the policy space that developing states require to implement developmental policies aimed at inequality reductions
A research report submitted in partial fulfilment of the requirements for the degree of Master of Laws (by Coursework and Research Report) at the University of the Witwatersrand,